Conservative management of central cemento-ossifying fibroma - Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Carrasco, Leandro Carlos; De Oliveiraz, Danila [UNESP]; Pereira, Járede Carvalho [UNESP]; Alcalde, Luis Fernando Azambuja; Faverani, Leonardo Perez [UNESP] (Wolters Kluwer, 2017)
Central cemento-ossifying fibroma is characterized by the combined production of osteoid and cementoid tissue. Radiographically, this lesion is presented as an outlined cortical and variable radiopaque spots, also can be present complete radiolucent or different degrees of radiopacity. The recommended treatment is curettage or enucleation, and the recurrence rate is less than 5%. Considering that surgical treatment is invasive, mainly in large lesions, this study aims to report a patient in whom conservative treatment was carried out by involving the preservation of teeth, with a long-term follow-up. A 48-year-old black female patient, diagnosed with central cemento-ossifying fibroma in mandible, treated conservatively and a 2 years of follow-up. It was concluded that the conservative treatment with a long term of follow-up for maintaining teeth was satisfactory.
Keywords: Mandible; Pathology; Surgery oral